Amiodarone and lung toxicity in a real-life contemporary population. (3rd October 2022) - Tsaban, G; Gordon, M; Omari, Y; Kezerle, L; Alnsasra, H; Buturlin, K; Bareza, S; Wagshal, A; Konnstantino, Y; Novack, V; Haim, M
Abstract: Background: Amiodarone-induced lung toxicity (ALT) is severe and potentially fatal. Most data on ALT are derived from previous decades when amiodarone was administrated chronically in higher doses, while currently, low-dose amiodarone 200 mg is routinely used. Whether low-dose amiodarone treatment is associated with ALT remains untested. Methods: This is a retrospective study among patients from the Southern district of Clalit Health Services (CHS) in Israel between 1st January 1999 and 1st July 2021. The study population comprised solely of patients with atrial fibrillation since this is the most prevalent condition for prescribing amiodarone. Patients treated with amiodarone were matched in a 1:1 manner with controls not exposed to amiodarone based on age, sex, living area, and atrial fibrillation diagnosis duration. To avoid immortal time bias, follow-up times of the matched controls were left adjudicated to truncate the amiodarone-free period of their matched cases. Patients with prior interstitial lung disease (ILD) were excluded. The primary outcome was the incidence of any ILD. We performed survival analyses using multivariable Cox regression controlling for potential confounders. Results: During the study period, 7, 048 patients who initiated amiodarone treatment were identified, of whom 6, 449 were matched with controls. The mean age was 71.5 years, and 46.4% were women among the matched population. The amiodarone-treatment group had higher rates of smoking (30.3% vs. 26.8%, p<0.001), rheumatic disease (4.5% vs. 3.5%, p=0.003), background myocardial infarction (31.6% vs. 19.6%), renal failure (17.2% vs. 10.8%) and congestive heart failure (33.8% vs. 20.7%; p<0.05 for all). During the study, with a mean follow-up time of 5.6 years, ILD occurred in 357 (5.5%) patients in the amiodarone group and 289 (4.5%) patients in the control group [adjusted hazard ratio: 1.09 (confidence interval 95%: 0.91, 1.3), p=0.4]. Conclusion: In a large contemporary real-life population, the incidence of ILD during 5.6 years was relatively low, and treatment with low-dose amiodarone was not associated with an increased risk of ILD. These results, if confirmed by other cohorts, may call for a change in the surveillance policy of patients treated with amiodarone Funding Acknowledgement: Type of funding sources: None.